Comprehensive reading instruction for students with learning disabilities: implications for teachers in inclusive education classrooms (2016)
Despite the critical role of good reading skills in the lives of all individuals, students with learning and specific reading disabilities often manifest deficits in the acquisition and use of diverse reading skills that are unexpected in relation to their age, cognitive ability, quantity and quality of instruction and intervention. This is particularly worrisome as these reading problems often go unnoticed during the primary school years. Once these students get to secondary school, their reading disabilities become more pronounced and its consequences further apparent to teachers and parents. Based on this problem, this paper discussed the need- for a comprehensive reading instruction for students with reading disabilities, the components of a comprehensive reading instruction and guidelines for a comprehensive reading instruction. Thus, it was concluded that no component of the reading skill should be downplayed. Moreover, this paper recommended among other things that teachers of students with learning and reading disabilities should conduct ongoing assessments to determine the actual nature of individual student reading disabilities. Thereafter, teachers of students with learning and reading disabilities should proceed with delivery of a balanced and comprehensive reading instruction that is guided by scientifically evidence-based procedures as discussed in this paper.